Assessment of heavy metal pollution of topsoil in settlement area, Darkhan city - Ch, Sonomdagva; Ch, Chultem; Ch, Byambatseren (Proceedings of the Mongolian Academy of Sciences, 2018)
This study was carried out to assess the content of toxic heavy metals (As, Co, Cr, Cu, Ni, Pb, V, Zn), determine pollution and spatial distribution of topsoil in Darkhan city which is one of the largest cities in Mongolia, to determine pollution and spatial distribution. The selected study area of Darkhan city was divided into 3 zones (industrial zones, ger districts or livestock breeding zones and private apartments or residential district zones) representing settlement’s characteristics, and 14 points were sampled from topsoil. In order to estimate the level of pollution, the contamination factor, the degree of contamination, pollution load index, and enrichment factor that were formulated by Hakanson, Tomlison, Selvaraj were used in our study. The results were come out by comparing the heavy metal concentration of the topsoil with it`s background concentration. In terms of spatial distribution of heavy metals in the topsoil, heavy metals concentration in ger district and industrial areas is relatively high, but pollution assessment is not very high. As a result of the enrichment factor which was used for assessment of contamination source, the average concentration of 8 elements (As, Co, Cr, Cu, Ni, Pb, V, Zn) at 13 points presented that was derived from natural sources.